2023
DOI: 10.32479/ijeep.14049
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Economic Growth and Energy Consumption Disaggregated by Sector: The Case of Morocco

Fatima Zahraa Tatou,
Yousfi Abdellah,
Rahaoui Tawfiq

Abstract: The type of relationship that can link energy with economic growth plays a major role in determining the macroeconomic policy of a country. Therefore, several studies have been carried out to derive econometric models to link energy consumption with gross domestic product (GDP). However, in these studies the energy consumption has been used in its global term, while this consumption includes all the economic sectors that use energy (residential, industry, transport, agriculture). Therefore, the objective of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Additionally, Moussavou (2022) found that electricity consumption has a bidirectional long-run causality with economic growth and a unidirectional long-run causality between energy consumption and capital stock. The Granger causality relationships between GDP and energy consumption were confirmed by Tatou et al (2023), with labour and capital causing GDP and energy consumption. Finally, Lee et al (2022) demonstrated that energy consumption, capital and labour positively influence manufacturing production individually and simultaneously.…”
Section: Literature Reviewmentioning
confidence: 86%
See 1 more Smart Citation
“…Additionally, Moussavou (2022) found that electricity consumption has a bidirectional long-run causality with economic growth and a unidirectional long-run causality between energy consumption and capital stock. The Granger causality relationships between GDP and energy consumption were confirmed by Tatou et al (2023), with labour and capital causing GDP and energy consumption. Finally, Lee et al (2022) demonstrated that energy consumption, capital and labour positively influence manufacturing production individually and simultaneously.…”
Section: Literature Reviewmentioning
confidence: 86%
“…Recent empirical studies show that the use of non-renewable energy promotes economic growth (Sek, 2017;Nawaz et al, 2021;de Oliveira & Moutinho, 2022;Tatou et al, 2023) but also impair environmental quality in the form of higher CO2 emissions and other hazardous gases (Bhat, 2018;Adedoyin et al, 2021;Asif et al, 2021;Karaaslan & Çamkaya, 2022;Solaymani et al, 2023). Conversely, the use of renewable energy improves environmental quality and mitigates CO 2 emissions (Ito, 2016;Adedoyin et al, 2021;Banga et al, 2022;Deka et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between gross domestic product (GDP) and energy consumption varies depending on the context, such as the country-level analysis, regional/sectoral analysis, the type of energy used, the income level, etc. Some empirical studies have found a positive relationship between energy consumption and GDP, suggesting that increased energy consumption can contribute to economic growth (Sek, 2017;Abbas, 2020;Andrieu et al, 2022;Zafirova & Angelova, 2022;Tatou et al, 2023). Similarly, Bulut & Apergis (2021) concluded that solar energy consumption has a positive impact on the GDP of the United States.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, Khan and Kong (2020) and Tatou et al (2023) found that the energy consumption of the transportation and residential sectors has a positive impact on GDP, while the energy consumption of households in Morocco has a negative impact on GDP. Tran et al (2022) discovered that GDP in the Czech Republic, Hungary and Slovakia is granger-caused by energy consumption, suggesting that energy consumption can drive economic growth.…”
Section: Literature Reviewmentioning
confidence: 99%